The effect of ascorbic acid supplementation on sperm quality, lipid peroxidation and testosterone levels of male Wistar rats - Sönmez, M; Türk, G; Yüce, A (Elsevier Science Inc, 2005)
This study was conducted to investigate the effects of ascorbic acid supplementation in drinking water on semen quality, lipid peroxidation and plasma testosterone level of male rats. In this investigation, 24 male Wistar rats were used. The animals were divided into three group, and 500, 250 and 0 (control) mg/kg/day ascorbic acid were supplemented with drinking water of rats in Groups A, B and C during 8 weeks, respectively. Ascorbic acid supplementation did not increase in the body weight and weights of the testis, epididymis, seminal vesicles and ventral prostate. Exogenous supplementation with ascorbic acid significantly increased (P < 0.05) the concentration of ascorbic acid in the testes and blood plasma, and the level of lipid peroxidation significantly decreased (P < 0.05) in these locations. There was no significant difference in spermatozoon motility among the three groups. However, epididymal sperm concentration and plasma testosterone level significantly increased (P < 0.05) in the ascorbic acid treated animals when compared to the control animals. The results suggest that ascorbic acid supplementation improves reproductive traits of male rats that are associated with high fertility. (c) 2004 Elsevier Inc. All rights reserved.
Keywords: ascorbic acid; rat; testosterone; epididymal sperm concentration